UNIVERSITIES AND THE TRANSITION TO AN INNOVATION ECONOMY IN THE RUSSIAN REGIONS - Valery P. Shestak (Высшее образование в России)
The article highlights the problem of the research activities of state universities, located in the Russian regions. Discusses the role of universities in socio-economic development ofregions in theprocess of transitionto innovative economy. The research activity of universities is considered within the model of the triple helix theory of innovation development. Proposes classification of scientific priorities, taking into account the interests of the regional economy and the conditions of scientific-pedagogical staff of universities in part, such as publication activity, the formation of the wage and the organization of students’ research work. It is assumed that the university can be an innovation hub of regional technological platforms.